PENGARUH KOMISARIS INDEPENDEN, KOMITE AUDIT DAN BLOCKHOLDERS TERHADAP EARNINGS MANAGEMENT (Studi Pada Emiten Sektor Manufaktur di Bursa Efek Indonesia) - Yani Zulvina; Amries Rusli Tanjung; Julita Saidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to provide empirical evidence about the influence of Independent Commissioners, Audit Committee and Blockholders to Earnings Management. The population in this study are manufacture company that listed in Indonesian Stock Exchange. Sampling was conducted using a purpossive sampling method and number of sampling is 36-years financial statements.. The method of data analysis used to test the hypothesis is multiple regression analysis using the program SPSS 17 version. Based on the formulation of the problem and hypotheses that have been built as well as the analysis of the results, it can be concluded that the independent commissioners, audit committee and blockholders simultaneously affect the earnings management, meaning jointly Independent Commissioners, Audit Committee and Blockholders can reduce Earnings Management. Thus, the Independent Commissioner, Audit Committee and Blockholders together (simultaneously) can improve the quality of financial reporting issuers manufacturing in Indonesian Stock Exchange.Keywords : Independent Commissioners, Audit Committee, Blockholders, and Earnings Management.